High-performance porous carbon-zeolite mixed-matrix membranes for CO₂/N₂ separation - Chuah, Chong Yang (2022)
Nano-sized PS-MFI, ETS-10 and SAPO-34 zeolites were utilized as CO2-selective fillers to fabricate high-performance mixed-matrix carbon molecular sieve membranes (CMSMs) for application in the CO2/N2 separation process. In this work, an in-house polyimide, ODPA-TMPDA, was used as a polymer precursor for CMSMs, due to its higher intrinsic gas permeability compared with commercial polyimides. Zeolite-filled CMSMs were then successfully fabricated without any appreciable defects at the filler/matrix interfaces. Gas permeation testing revealed that both CO2 permeability and CO2/N2 selectivity can be significantly improved upon incorporation of such zeolite fillers, enabling selective adsorption and transport of CO2. In particular, SAPO-34 yielded the best results among the zeolite fillers tested, resulting in an excellent performance far beyond the Robeson upper bound limit for CO2/N2 separation.